Pengukuran Kesesuaian Titik Transit BRT Pada Koridor Simpang Lima - Terminal Penggaron Dengan Konsep Transit Oriented Development - Fauzia Lutfihandayani; Yudi Basuki (Jurusan Perencanaan Wilayah dan Kota, 2022)
Semarang is the center of government and the center of economic activity in Central Java. The rapidly developing Semarang economy is characterized by an increasing number of in-migration, employment, the quality of education and infrastructure development. These developments led to an increase in the intensity of human movement, which was reflected in an increase in traffic flow dominated by private vehicles. The increasing use of private vehicles can affect the efficiency of the urban economy. One of the efforts in dealing with these problems is by providing public transportation such as BRT. BRT is a manifestation of the development of a public transportation system that supports the concept of Transit Oriented Development (TOD). TOD has a development orientation at the transit point and is surrounded by a high-intensity built-up area with a radius of 400 - 800 meters. To be able to find out whether the transit point in Semarang is in accordance with the development objectives that support TOD, a transit point measurement with the TOD concept in Semarang is measured. The research method used is a quantitative approach with scoring, weighting and spatial analysis methods.The measurement results show that 8% of transit points are in accordance with their application in supporting the concept of Transit Oriented Development with a percentage of transit points that are quite appropriate at 61%, which means that transit points are able to support the transportation system with the concept of Transit Oriented Development. Transit points that are still not appropriate in implementing Transit Oriented Development by 31% of transit points so that it needs to be considered in order to be adapted to local policies to be able to support the transportation system with the concept of Transit Oriented Development. Almost all transit points meet the TOD principle with the use of heterogeneous land use, easy access in changing public transportation modes and designs that support pedestrian and bicycle activities. Only two transit points are included in the